2020
DOI: 10.1158/1078-0432.ccr-20-2859
|View full text |Cite
|
Sign up to set email alerts
|

STK11/LKB1 Mutations in NSCLC Are Associated with KEAP1/NRF2-Dependent Radiotherapy Resistance Targetable by Glutaminase Inhibition

Abstract: Purpose: Radiotherapy (RT) with or without chemotherapy is a mainstay of treatment for locally advanced non-small cell lung cancer (NSCLC), but no predictive markers are currently available to *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 50 publications
(81 reference statements)
0
37
0
Order By: Relevance
“…Locally advanced NSCLC is often treated with radiotherapy with or without chemotherapy. A recent study by Sitthideatphaiboon et al investigated the association between STK11 mutations in stage III NSCLC and outcomes after radiotherapy in a population of 194 patients [ 47 ]. After a median follow-up of four years, the study found that STK11 mutations were associated with a significantly higher locoregional recurrence rate (LRR, p=0.0108) and shorter disease-free survival (DFS; HR 2.53; [1.37-4.65], p=0.002).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Locally advanced NSCLC is often treated with radiotherapy with or without chemotherapy. A recent study by Sitthideatphaiboon et al investigated the association between STK11 mutations in stage III NSCLC and outcomes after radiotherapy in a population of 194 patients [ 47 ]. After a median follow-up of four years, the study found that STK11 mutations were associated with a significantly higher locoregional recurrence rate (LRR, p=0.0108) and shorter disease-free survival (DFS; HR 2.53; [1.37-4.65], p=0.002).…”
Section: Reviewmentioning
confidence: 99%
“…LKB1 loss increases downstream production of NRF2, which, in turn, reduces reactive oxygen species (ROS) levels. Because radiation treatment relies on the destruction of tumor cells via intracellular ROS damage, tumor cells with these mutations can resist high levels of treatment [ 47 ].…”
Section: Reviewmentioning
confidence: 99%
“…Tumor cells, in contrast to non-transformed cells, frequently harbor mutations in check point genes and fail to halt the cell cycle to initiate the repair of damaged DNA 5053 . Mutations in oncogenes, such as KRAS 54 ; and subsets of loss-of-function mutations in tumor suppressors, such as FBXW7 44, 55 or STK11 56 , can cause resistance to DNA damage based therapies. Identification of exploitable ‘bottlenecks’ for tumor cell survival might be an option to advance our current treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 In lung cancers, Nrf2 gain-of-function mutations often occur, and higher intratumoral levels of Nrf2 are associated with poor clinical outcomes. [33][34][35][36] However, currently, little evidence is available on the effect of DADS on Nrf2 expression in response to radiation. Whether and how DADS influences IR-induced migration and invasion in NSCLC is still unknown.…”
Section: Introductionmentioning
confidence: 99%